Legal Protection For Illegal Indonesian Migrant Workers Victims Of Human Trafficking - Yeti Kurniati (SEAN Institute, 2023)
Legal protection for victims of human trafficking has become a serious concern for the international community because human trafficking does not only occur in one area but has developed into an organized transnational crime. But what happens if the victims are illegal migrant workers who incidentally do not have official documents, considering that the number of illegal migrant workers who are victims of human trafficking abroad is currently increasingly dominating. The purpose of this study is to determine legal protection for illegal Indonesian migrant workers who are victims of trafficking in persons in connection with Law Number 21 of 2007. The author uses a normative juridical research method that uses secondary data and uses primary data only as support for secondary data. The results of this study indicate that Law Number 21 of 2007 concerning the Crime of Trafficking in Persons, hereinafter referred to as the TPPO Law, provides legal protection to illegal Indonesian migrant workers who are victims of human trafficking in the form of fulfilling their rights, including the right to rehabilitation, the right to integrated services, the right to be returned to Indonesia based on state costs, the right not to be arbitrarily deported, the right to assistance when dealing with laws in the destination country, the right to restitution, and other rights.